Perspektif Masyarakat Terhadap Dampak dari Aktivitas Pertambangan - Aldiyansyah, Yudi; Rianto, Doli Jumat; Permana, Irfan Satria; Kutni, Darul; Marwadi, Aji (Innovative: Journal Of Social Science Research, 2025)
Mining activities are one of the industrial sectors that are capital and technology intensive. This sector provides substantial economic benefits and also has significant environmental, economic and social impacts. This study aims to analyze community perspectives and the impacts felt by the community due to mining activities. The methodology of this research uses a quantitative research type with a sample size of 99 respondents. Perceptions are given in the form of a Likert scale to measure the level of validity, reliability and t-test (influence). The results of the study show that mining activities have brought significant positive changes to people's lives, especially increased income, changes in types of work, opening up employment opportunities and improving the quality of education, besides that it also has significant negative impacts, namely air pollution, noise, land damage, environmental pollution. Due to the magnitude of the negative impacts, preventive measures and environmental management must be carried out as early as possible to prevent widespread land damage.